Countering Ahok, Countering the Public: An Investigation of Counter-public Sphere in the Cyberspace (Faculty of Social Science, Universitas Negeri Semarang, 2017)
This paper analysis how Buni Yani used social media – in this case his Facebook account - to counter the Indonesian mainstream public sphere in order to challenge its domination that predominantly started series of Islamic rallies in Jakarta Aksi Bela Islam by the end of 2016. Using the theory of public sphere as described by Gerhards and Neidhardt (1990) and its transfer to the realm of Internet (Gerhards Schäfer, 2009), this paper shows that Buni Yani used all the three stages of public spheres as explained in the theory: encounters, public events, and mass media communication to successfully force a political issue into the arena of debate in the communication system and in the end changed the political outcome in Jakarta: Ahok’s detainment and consequently his inability to hold his Governor post any longer. The strategic communication by Buni Yani was not only successful to offer/force a new topic in the public daily communication but also to mobilize thousands of Islamic sympathizers in a series of demonstrations to support his view. All the materials used for this analyses are mainly obtained from online sources.